Pola Pembelajaran Sunnah Nabi di TK Islam dan SD Islam Terpadu - Nur Laily Fauziyah (Almarhalah, 2017)
Today we witness that students are still activated by their cognitive abilities, namely memorizing at a glance, classes are too dense with general material content, very poor motivation, equipped with religious knowledge but only limited to the delivery without practice or practice accompanied by deep appreciation. Outside the classroom, promiscuity is everywhere, games through gadgets are familiar to young children, as well as a lack of control and supervision and attention from parents, so that all of them make children behave badly, commit crime, spree and so on. The purpose of this study was to determine the learning patterns of the sunnah of the prophet at the level of kindergarten and elementary school education, and to know the sunnah-sunnah of the prophet taught in Islamic kindergarten and integrated Islamic elementary school. From the results of this research study, there are obtained good and effective learning patterns and some of the sunnah of the Prophet relating to good social ethics and can be applied by educators, especially both parents who want to crave their children to be proud or qurrota a'yun for all families, be a beloved people of the Prophet Muhammad. One of the characteristics of people who love the Prophet is fond of memorizing, spreading and practicing his sunnahs. With all that stock, he will get happiness in the world and the hereafter and get the Prophet's intercession to be able to get together in heaven.